Electrode precursor composition
By using the electrode precursor composition of the multimodal dispersed phase, gel electrodes with high energy density and safety are prepared, which solves the safety risks of liquid electrolytes in traditional lithium-ion batteries and the high energy consumption of the solvent casting process.
Patent Information
- Application Number
- CN202380060068.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-31
- Filing Date
- 2023-08-25
- Publication Date
- 2025-03-14
AI Technical Summary
The use of liquid electrolytes in traditional lithium-ion batteries poses safety risks, and the solvent casting process consumes high energy, so it is necessary to avoid the use of sacrificial solvents.
The gel electrode is prepared by heat treatment by using a multimodal dispersed phase to reduce the use of liquid electrolytes using a multimodal dispersed phase, including a polymer-solvent gel matrix phase and a dispersed phase of an electrochemically active material.
It improves the energy density and safety of the electrodes, reduces the fire risk of the battery cells, and reduces the energy consumption of the electrode production process.
Smart Images

Figure CN119631187A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an electrode precursor composition for an alkali metal ion secondary battery cell, an electrode, a battery cell and an energy storage device made from the precursor composition, and a method for preparing an electrode for an alkali metal ion secondary battery cell. Background Art
[0002] Lithium-ion secondary batteries are the leading battery technology used today in applications ranging from small personal devices to electric vehicles. Lithium-ion batteries are favored for their high energy density and long cycle life. They contain multiple lithium-ion secondary battery cells, which is an example of an alkali metal ion secondary battery cell.
[0003] Conventional lithium-ion battery components, such as electrodes, are made by a solvent casting process that uses sacrificial solvents. This is an energy-expensive step, so a process that avoids the use of sacrificial solvents is desirable.
[0004] Another major disadvantage of lithium-ion technology and other alkali metal ion secondary battery cell technologies is that liquid electrolytes are often used in the lithium-ion battery cells of the battery to provide conductivity of lithium ions in the battery cell between the solid, solvent-cast anode and cathode. This leads to safety issues because liquid electrolytes are often highly flammable. This is a particular problem for electric vehicles, where a collision with another vehicle may be relatively large and the resulting impact may cause battery damage and electrolyte ignition. This is also a problem for household devices, as a lithium-ion battery fire may cause property damage or serious injury.
[0005] One approach to avoid the use of sacrificial solvents and the need for liquid electrolytes within the battery cell is to prepare gel electrodes. These electrodes can be formed from a composition prepared by mixing the necessary components such as electrochemically active materials, polymers, and liquid electrolytes, and then heat treating the composition.
[0006] The gel electrode can be made from the precursor composition by thermal treatment, such as hot rolling or extrusion. The energy density of the final electrode is determined at least in part by the loading of the electrochemically active material within the gel electrode. As the loading of the electrochemically active material within the precursor composition increases, the amount of force required to form an electrode film of a given thickness rises exponentially, all other things being equal. At a certain loading of electrochemically active material, the forces involved in hot rolling of the precursor material make it impossible to form the final electrode product, for example due to damage to the support film, damage to the gel electrode itself (e.g., rupture or decomposition of the electrode), or exceeding the limits of the ability of the roller assembly to process the material into a film.
[0007] There is a need for gel electrode precursor compositions that are easier to handle and that can be processed into high energy density electrodes. Summary of the invention
[0008] The present invention generally relates to electrode precursor compositions for alkali metal ion secondary battery cells, and more particularly to electrode precursor compositions comprising a multimodal dispersed phase comprising an electrochemically active material.
[0009] A first aspect of the present invention is an electrode precursor composition for an alkali metal ion secondary battery cell, comprising:
[0010] a polymer-solvent gel matrix phase; and
[0011] a dispersed phase comprising an electrochemically active material;
[0012] Among them, the electrochemically active material has D 1 50 / D 2 50 Multimodal particle size distribution ranging from 2 to 15;
[0013] Among them, D 1 50 is the volume median diameter of the first particle mode in the distribution, D 2 50 is the volume median diameter of the second particle mode within the distribution.
[0014] The electrode precursor can be used as a precursor material for preparing a gel electrode.
[0015] The electrode precursor composition comprises a polymer-solvent gel matrix phase and a dispersed phase of solid particulate materials dispersed throughout the matrix phase. In this way, the electrode precursor composition has a gel-like composition and can be processed into a thin film electrode having a similar gel-like composition, wherein the electrode structure comprises a solvent component, such as a liquid electrolyte trapped in the matrix phase due to the gelling properties of the polymer. Conventional solvent-cast electrodes formed by casting a slurry solvent onto a substrate and then drying require the separate addition of free liquid electrolyte to the battery cell during assembly, resulting in a battery cell with a fire risk due to the flammability of the free liquid electrolyte. Replacing such solvent-cast electrodes with gel electrodes prepared from the precursor composition of the present invention reduces this risk and provides a battery cell with increased safety.
[0016] It has been found that the use of a gel electrode precursor composition comprising a D 1 50 / D 2 50 The multimodal particle size distribution of the dispersed phase allows the active material loading of the electrode precursor composition to be increased to a higher level than is possible when a unimodal particle size distribution is used. Without wishing to be bound by theory, it is believed that for D 150 / D 2 50 This particle size distribution in the range of 2 to 15 allows for a particularly efficient packing of the active material particles, which allows for an increased material loading and lower than expected forces exerted on the hot rollers during processing. As a result, it is possible to manufacture electrodes of a given thickness with a higher active material loading and therefore a higher energy density. In addition, due to the reduced load on the heat treatment equipment (e.g., hot rollers or extrusion dies), the electrode production process requires lower energy and is therefore cheaper and more environmentally friendly.
[0017] The multimodal distribution also improves the fluidity of the electrode composite or gel composite before heat treatment, thereby facilitating the handling.
[0018] The term "multimodal particle size distribution" means a particle size distribution that contains two or more different peaks in a distribution with a maximum value at different particle sizes. One of the peaks can be a distinct shoulder of another peak (with a distinct maximum), or the peaks can be substantially non-overlapping, such as an area of less than 30%, less than 25%, or less than 20% of a peak can overlap with another peak. The term "bimodal particle size distribution" means a particle size distribution that contains just two different peaks in a distribution with a maximum value at different particle sizes. One of the peaks can be a distinct shoulder of another peak (with a distinct maximum), or the peaks can be substantially non-overlapping, such as an area of less than 30%, less than 25%, or less than 20% of a peak can overlap with a second peak.
[0019] The term "particle mode" or "mode" refers to a peak in a bimodal or multimodal particle size distribution that represents the contribution of a single population of particles within the overall distribution.
[0020] The preferred and / or optional features of the present invention will now be described. Unless the context otherwise requires, any aspect of the present invention may be combined with any other aspect of the present invention. Any preferred and / or optional features of any aspect may be combined with any aspect of the present invention individually or in combination, unless the context otherwise requires.
[0021] In some embodiments, the ratio of the volume fraction of the first particle mode (having a larger particle size) to the volume fraction of the second particle mode (having a smaller particle size) is 0.6 to 15, for example 0.6 to 12, for example 0.6 to 10, for example 1.0 to 10, for example 1.2 to 9.5 or 2 to 4.
[0022] In some embodiments, the ratio of the volume fraction of the first particle mode (having a larger particle size) to the volume fraction of the second particle mode (having a smaller particle size) is 0.6 to 1.0, such as 0.6 to 0.9, 0.6 to 0.8, or 0.7 to 0.8.
[0023] It has been found that this ratio of the volume fraction of the first particle mode to the volume fraction of the second particle mode provides particular improvements in active material loading and ultimate energy density.
[0024] In some embodiments, the mass ratio of the first particle mode to the second particle mode is about 60:40 to about 90:10, such as about 65:35 to about 75:25.
[0025] In some embodiments, the electrochemically active material has D 1 50 / D 2 50 A multimodal particle size distribution in the range of 2 to 10, such as 2 to 8, 2 to 7, 2 to 6, 2 to 5, or 2 to 4. In some embodiments, the electrochemically active material has a D 1 50 / D 2 50 Multimodal particle size distribution in the range of 2.5 to 3.5.
[0026] In some embodiments, the electrochemically active material has D 1 50 / D 2 50 Multimodal particle size distribution in the range of 2 to 14, e.g., 4 to 14, 2 to 12, 4 to 12, 2 to 10, 4 to 10, 5 to 12, 5 to 10, 5 to 8, e.g., 6 to 8 or 6.5 to 7.5 or about 7.
[0027] In some embodiments, the electrochemically active material has D 1 50 / D 2 50 Multimodal particle size distribution in the range of 4 to 15, such as 7 to 15.
[0028] In some embodiments, the electrochemically active material has D 1 模式 / D 2 模式 Multimodal particle size distribution in the range of 2 to 15, where D 1 模式 is the volume modal size of the first particle mode in the distribution, D 2 模式 is the volume modal particle size of the second particle mode in the distribution. In some embodiments, the electrochemically active material has D 1 50 / D 2 50 A multimodal particle size distribution in the range of 2 to 10, e.g., 2 to 8, 2 to 7, 2 to 6, 2 to 5, or 2.5 to 4.5.
[0029] In some embodiments, the mass ratio of the first particle mode to the second particle mode is about 65:35 to about 75:25, and the electrochemically active material has a D 1 50 / D 2 50 Multimodal particle size distribution in the range of 6 to 8.
[0030] In some embodiments, the electrochemically active material constitutes at least 60% by volume of the electrode precursor composition, e.g., at least 61%, at least 62%, at least 63%, at least 64%, at least 65%, at least 66%, at least 67%, or at least 68% by volume.
[0031] Comparative electrode precursor compositions containing only a monomodal distribution of active material cannot achieve high loading of active material and cannot be processed into electrodes loaded above 60% by volume. In contrast, the electrode precursor compositions of the present invention allow for at least 62% by volume loading of active material, and in some cases up to 68% by volume.
[0032] In some embodiments, the electrochemically active material comprises 50 to 75 volume %, eg, 50 to 70 volume %, 50 to 69 volume %, 50 to 68 volume %, 55 to 68 volume %, 58 to 68 volume %, or 60 to 68 volume % of the electrode precursor composition.
[0033] In some embodiments, the electrochemically active material comprises 62 to 75 volume %, eg, 62 to 70 volume %, 62 to 69 volume %, 62 to 68 volume %, or 64 to 69 volume % of the electrode precursor composition.
[0034] The volume median particle size (D 1 50 ) and the volume median particle size (D 2 50 ) is not particularly limited as long as the above ratio is met.
[0035] However, in some embodiments, the volume median particle size (D 1 50 ) is 5 to 50 μm, for example, 5 to 40 μm, 5 to 30 μm, 5 to 25 μm, 5 to 20 μm or 10 to 20 μm.
[0036] In some embodiments, the volume median particle size (D 2 50 ) is 0.5 to 10 μm, for example, 0.5 to 8 μm, 0.5 to 7 μm, 1 to 7 μm, 2 to 7 μm or 3 to 7 μm.
[0037] The volume modal particle size of the first particle mode in the distribution (D 1 模式 ) and the volume modal particle size of the second particle mode within the distribution (D 2 模式 ) is not particularly limited in its absolute value.
[0038] However, in some embodiments, the volume modal particle size (D 1 模式 ) is 5 to 50 μm, for example, 5 to 40 μm, 5 to 30 μm, 5 to 25 μm, 5 to 20 μm, 5 to 15 μm or 9 to 15 μm.
[0039] In some embodiments, the volume median particle size (D 2 50 ) is 0.5 to 10 μm, for example, 0.5 to 8 μm, 0.5 to 7 μm, 1 to 7 μm, 2 to 7 μm or 2 to 5 μm.
[0040] D 1 50 and D 2 50 is the volume median particle size. In other words, they represent the particle size in microns that divides the volume distribution of the particle population in half, with 50% by volume of the particles having a size below this value and 50% by volume of the particles having a size above this value. Therefore, D 1 50 is the particle size in micrometers that divides the volume distribution of the first particle mode in half, with 50% by volume of the particles having a particle size below D 1 50 Value, 50% by volume of the particles have a particle size greater than D 1 50 Value. 2 50 is the particle size in micrometers that divides the volume distribution of the second particle mode in half, with 50% by volume of the particles having a particle size below D 2 50 Value, 50% by volume of the particles have a particle size greater than D 2 50 value.
[0041] D 1 模式 and D 2 模式 are the volume modal particle sizes. In other words, they represent the peak position in the particle size distribution and represent the most common particle size in the distribution. Therefore, D 1 模式 is the particle size value when the first particle mode of the distribution reaches the peak, D2 模式 It is the particle size value when the second particle mode of the distribution reaches its peak.
[0042] The skilled person will understand that the volume median particle size D 1 50 and D 2 50 And the volume modal particle size D 1 模式 and D 2 模式 It can be measured using a Malvern Mastersizer 3000 using the light scattering method set forth in ASTM B822-20, applying Mie scattering theory.
[0043] The skilled person will also appreciate that for particle compositions comprising a multimodal particle size distribution (e.g. bimodal), the PSD may be deconvoluted to calculate the volume median particle size for each particle mode using simple techniques well known to the skilled person.
[0044] In some embodiments, the dispersed phase further comprises a conductive additive. This may be a particulate conductive additive.
[0045] In some embodiments, the conductive additive comprises or consists of a carbon additive. In some embodiments, the conductive additive comprises or consists of one or more of carbon black and graphite. In some embodiments, the conductive additive comprises or consists of carbon black. Examples of commercially available carbon black include Ketjen Black and Super C65.
[0046] In some embodiments, the conductive additive is present in an amount of 1.5 wt % to 2.5 wt % based on the total weight of the electrode precursor composition.
[0047] In some embodiments, the conductive additive is present in an amount of 1.5 vol% to 2.5 vol%, e.g., 1.5 vol% to 2.5 vol%, 1.5 vol% to 2.4 vol%, 1.5 vol% to 2.3 vol%, 1.5 vol% to 2.2 vol%, 1.5 vol% to 2.1 vol%, or 1.6 vol% to 2.1 vol%, based on the total weight of the electrode precursor composition.
[0048] In some embodiments, the dispersed phase comprises 2 vol% to 4 vol% of the conductive additive, e.g., 2.1 vol% to 3.9 vol%, 2.2 vol% to 3.8 vol%, 2.3 vol% to 3.7 vol%, 2.3 vol% to 3.6 vol%, 2.3 vol% to 3.5 vol%, or 2.4 vol% to 3.5 vol%, based on the total volume of the dispersed phase.
[0049] In some embodiments, the dispersed phase comprises 96 to 98 vol% electrochemically active material, e.g., 96.1 to 97.9 vol%, 96.2 to 97.8 vol%, 96.3 to 97.7 vol%, 96.3 to 97.6 vol%, 96.3 to 97.5 vol%, or 96.4 to 97.5 vol%, based on the total volume of the dispersed phase.
[0050] The dispersed phase may consist of an electrochemically active material and a conductive additive. In some embodiments, the dispersed phase consists of an electrochemically active material and carbon black.
[0051] In some embodiments, the polymer-solvent gel matrix phase comprises a mixture of a gelling polymer and a solvent component, wherein the weight ratio of solvent component:polymer is 2 to 6.
[0052] In some embodiments, the electrode precursor composition includes the gelling polymer in an amount of 5 to 10 vol %, such as 5 to 9 vol %, 5 to 8 vol %, 5.5 to 8 vol %, or 6 to 8 vol %, based on the total volume of the electrode precursor composition.
[0053] In some embodiments, the polymer-solvent gel matrix phase comprises the gelling polymer in an amount of 15 to 25 vol%, e.g., 15 to 24 vol%, 16 to 24 vol%, 17 to 24 vol%, 17 to 23 vol%, 18 to 23 vol%, 18 to 22 vol%, 19 to 22 vol%, 19 to 21 vol%, or about 20 vol%, based on the total volume of the polymer-solvent gel matrix phase.
[0054] In some embodiments, the polymer-solvent gel matrix phase comprises the solvent component in an amount of 75 to 85 volume %, e.g., 75 to 84 volume %, 76 to 86 volume %, 77 to 84 volume %, 77 to 83 volume %, 78 to 83 volume %, 78 to 82 volume %, 79 to 82 volume %, 79 to 81 volume %, or about 80 volume %, based on the total volume of the polymer-solvent gel matrix phase.
[0055] In some embodiments, the electrode precursor composition includes the solvent component in an amount of 20 to 35 vol %, eg, 21 to 34 vol %, 22 to 33 vol %, 23 to 32 vol %, or 24 to 31 vol %, based on the total volume of the electrode precursor composition.
[0056] In some embodiments, the polymer-solvent gel matrix phase consists of a gelling polymer and a solvent component.
[0057] In certain embodiments, solvent component comprises the solvent that comprises one or more cyclic or linear carbonate compounds or is made up of it.In certain embodiments, solvent comprises one or more cyclic carbonate compounds.In certain embodiments, solvent comprises one or more of following: ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl carbonate-methyl ester, butylene carbonate, vinylene carbonate, fluoroethylene carbonate, fluoropropylene carbonate and gamma-butyrolactone.
[0058] In some embodiments, the solvent component further includes a lithium salt component. In some embodiments, the lithium salt component includes one or more of the following: lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluoro(oxalate)borate (LiDFOB), lithium difluorophosphate, lithium bis(oxalate)borate, LiBF4, and 2-trifluoromethyl-4,5-dicyanoimidazole lithium (LiTDI). In the case where the solvent component includes a solvent and a lithium salt component, the solvent component may also be described as an electrolyte component.
[0059] In some embodiments, the electrolyte component is a composition comprising:
[0060] (a) 5-35 wt% lithium salt
[0061] (b) 2-10 wt % of additives; and
[0062] (c) 55-93% by weight of a solvent;
[0063] Among them, lithium salts include:
[0064] (ai) a salt selected from the group consisting of lithium 2-trifluoromethyl-4,5-dicyanoimidazole, lithium difluoro(oxalato)borate, lithium bis(oxalato)borate and lithium tetrafluoroborate; and optionally,
[0065] (aii) a co-salt selected from the group consisting of lithium bis(trifluoromethanesulfonyl)imide and / or lithium bis(fluorosulfonyl)imide;
[0066] wherein the molar ratio of the salt to the co-salt is 100:0 to 5:95; provided that the composition does not contain lithium bis(fluorosulfonyl)imide and lithium difluoro(oxalate)borate or lithium tetrafluoroborate;
[0067] and wherein the additive comprises vinylene carbonate and optionally fluoroethylene carbonate;
[0068] And wherein the solvent comprises (ci) ethylene carbonate and 10-30 mol % of propylene carbonate, or (cii) γ-butyrolactone and optionally ethylene carbonate.
[0069] In some embodiments, the lithium concentration in the electrolyte component is between about 0.5M and 2.0M, such as between about 0.7M and 2.0M.
[0070] In some embodiments, the electrolyte components consist of (a) 5-35 wt % of a lithium salt; (b) 2-10 wt % of an additive; and (c) 55-93 wt % of a solvent.
[0071] In some embodiments, the additive in the electrolyte component consists of 30-90 mol % of fluoroethylene carbonate and 10-70 mol % of vinylene carbonate.
[0072] In some embodiments, the solvent in the electrolyte component consists of (ci) 70-90 mol % ethylene carbonate and 10-30 mol % propylene carbonate, or (cii) 10-100 mol % γ-butyrolactone and optionally 0-90 mol % ethylene carbonate.
[0073] In some embodiments, the electrolyte composition comprises 5-25 wt % of a lithium salt, 2-10 wt % of an additive, and 65-93 wt % of a solvent; wherein,
[0074] (a) the lithium salt comprises 20-100 mol % of lithium tetrafluoroborate and 0-95 mol % of lithium bis(trifluoromethanesulfonyl)imide;
[0075] (b) the additive comprises 30-90 mol % of fluoroethylene carbonate and 10-70 mol % of vinylene carbonate; and
[0076] (c) The solvent comprises 70-90 mol % of ethylene carbonate and 10-30 mol % of propylene carbonate.
[0077] In some embodiments, the electrolyte composition comprises 5-25 wt % of a lithium salt, 2-10 wt % of an additive, and 65-93 wt % of a solvent; wherein,
[0078] (a) the lithium salt comprises a mixture of 20-100 mol % of lithium 2-trifluoromethyl-4,5-dicyanoimidazole and lithium bis(oxalato)borate, and 0-95 mol % of lithium bis(fluorosulfonyl)imide;
[0079] (b) the additive comprises 30-90 mol % of fluoroethylene carbonate and 10-70 mol % of vinylene carbonate; and
[0080] (c) The solvent comprises 70-90 mol % of ethylene carbonate and 10-30 mol % of propylene carbonate.
[0081] In some embodiments, the electrolyte composition comprises 15-35 wt % of a lithium salt, 2-10 wt % of an additive, and 55-83 wt % of a solvent; wherein,
[0082] (a) the lithium salt comprises a mixture of 5-100 mol % of lithium 2-trifluoromethyl-4,5-dicyanoimidazole and lithium bis(oxalato)borate, and 0-95 mol % of lithium bis(fluorosulfonyl)imide;
[0083] (b) the additive comprises 30-90 mol % of fluoroethylene carbonate and 10-70 mol % of vinylene carbonate; and
[0084] (c) The solvent contains 0-90 mol % of ethylene carbonate and 10-100 mol % of γ-butyrolactone.
[0085] In some embodiments, the solvent component consists of one or more cyclic or linear carbonate compounds and a lithium salt.
[0086] In some embodiments, the polymer-solvent gel matrix phase constitutes 20% to 50% by volume of the electrode precursor composition, e.g., 25% to 45% by volume, 28% to 42% by volume, 30% to 40% by volume, 31% to 49% by volume, or 32% to 48% by volume.
[0087] The nature of the electrochemically active material is not particularly important in the present invention. The benefits of the present invention based on the specific multimodal particle size distribution of the active material can be realized for any active material that may be present in the electrode composition. The skilled person will be aware of a large number of possible electrochemically active materials, including cathode active materials (also known as positive electrode active materials) and anode active materials (also known as negative electrode active materials), which can be used in the present invention.
[0088] The electrochemically active material is a particulate material, ie a material consisting of a plurality of discrete particles. The particles may include primary particles and / or secondary particles formed by the aggregation of a plurality of primary particles.
[0089] In some embodiments, the electrochemically active material is a cathode active material.
[0090] In some embodiments, the positive electrode active material is a lithium transition metal oxide material. In some embodiments, the positive electrode active material is a lithium transition metal oxide material, which comprises a mixed metal oxide of lithium and one or more transition metals, and optionally further comprises one or more additional non-transition metals. In some embodiments, the positive electrode active material is a lithium transition metal oxide material comprising lithium and one or more transition metals selected from nickel, cobalt and manganese. In some embodiments, the positive electrode active material is selected from one or more of the following: lithium cobalt oxide (LCO), lithium manganese oxide (LMO), lithium nickel cobalt oxide (NCO), aluminum-doped lithium nickel cobalt oxide (NCA), lithium nickel manganese cobalt oxide (NMC), lithium nickel oxide (LNO), lithium nickel manganese oxide (LNMO), lithium iron phosphate (LFP), lithium manganese iron phosphate (LFP) and lithium nickel vanadate (LNV). In some embodiments, the positive electrode active material is lithium nickel manganese cobalt oxide (NMC), optionally doped with another metal, such as aluminum.
[0091] In some cases, the electrochemically active material may include carbon, suitably graphite, graphene, or a mixture of carbon and silicon oxide.
[0092] Such electrochemically active materials are commercially available or can be made by methods known to those skilled in the art, for example by precipitation of a mixed metal hydroxide intermediate from a reaction mixture containing various precursor metal salts, followed by calcination to form a mixed metal oxide, and optionally lithiated to incorporate lithium into the oxide.
[0093] The electrochemically active material may be undoped or uncoated, or may include one or more dopants and / or coatings. For example, the electrochemically active material may be doped with a small amount of one or more metallic elements. The electrochemically active material may include a carbon coating on the surface of the material particles.
[0094] In some embodiments, the electrochemically active material is a negative electrode active material.
[0095] In some embodiments, the electrochemically active material has a bimodal particle size distribution.
[0096] The polymer-solvent gel matrix phase comprises a gel matrix formed by swelling of the swellable polymer when the polymer absorbs the solvent. Thus, the polymer-solvent gel matrix phase comprises a gel comprising the polymer and the absorbed solvent.
[0097] In some embodiments, the polymer-solv gel matrix phase comprises one or more gelling polymers selected from the group consisting of poly(ethylene glycol dimethacrylate), poly(ethylene glycol diacrylate), poly(propylene glycol dimethacrylate), poly(propylene glycol diacrylate), poly(methyl methacrylate) (PMMA), poly(acrylonitrile) (PAN), polyurethane (PU), poly(vinylidene fluoride) (PVdF), poly(vinylidene fluoride-hexafluoropropylene) (PvDF-HFP), poly(ethylene oxide) (PEO), poly(ethylene glycol dimethyl ether), poly(ethylene glycol diethyl ether), poly[bis(methoxyethoxyethoxy)-phosphazene], poly (dimethylsiloxane) (PDMS), polyacene, polydisulfide, polystyrene, polystyrene sulfonate, polypyrrole, polyaniline, polythiophene, polythiophene, polyvinylpyridine (PVP), polyvinyl chloride (PVC), polyaniline, poly(3,4-ethylenedioxythiophene) (PEDOT), poly(p-phenylene), poly(triphenylene), polyazepine, polyfluorene, polynaphthalene, polyanthracene, polyfuran, polycarbazole, tetrathiafulvalene-substituted polystyrene, ferrocene-substituted polyethylene, carbazole-substituted polyethylene, polyoxyphenazine, poly(heteroacene), poly[(4-styrenesulfonyl)(trifluoromethanesulfonyl)imide-co-methoxy-polyethylene glycol acrylate] (Li[PSTFSI-co-MPEGA]), sulfonated polyphenylene oxide (PPO), N,N-dimethylacrylamide (DMAAm), lithium 2-acrylamido-2-methyl-1-propane sulfonate (LiAMPS), poly(2-acrylamido-2-methylpropane sulfonate-co-vinyltriethoxysilane), polyethylene oxide (PEO) / poly(lithium sorbate), PEO / poly(lithium mucate), PEO / [polysorbate)+BF3), PEO copolymers, PEO terpolymers, and NIPPONSHOKUBAI® polymers.
[0098] In some embodiments, the polymer-solvent gel matrix phase comprises PMMA. In some embodiments, the polymer-solvent gel matrix phase comprises ultra-high molecular weight PMMA, for example, with a molecular weight greater than 100 kDa.
[0099] In some embodiments, the electrode precursor composition is for a lithium ion secondary electrochemical cell. In some embodiments, the electrode precursor composition is a cathode precursor composition.
[0100] A second aspect of the present invention is an electrode for an alkali metal ion secondary battery cell, comprising:
[0101] a polymer-solvent gel matrix phase; and
[0102] a dispersed phase comprising an electrochemically active material;
[0103] Among them, the electrochemically active material has D 150 / D 2 50 Multimodal particle size distribution ranging from 2 to 15;
[0104] Among them, D 1 50 is the volume median diameter of the first particle mode in the distribution, D 2 50 is the volume median diameter of the second particle mode within the distribution.
[0105] In some embodiments, the electrode is produced by processing the electrode precursor composition according to the first aspect to form a film.
[0106] Thus, the electrode may include a polymer-solvent gel matrix phase; and
[0107] The dispersed phase comprises an electrochemically active material;
[0108] Among them, the electrochemically active material has D 1 50 / D 2 50 Multimodal particle size distribution ranging from 2 to 15;
[0109] Among them, D 1 50 is the volume median diameter of the first particle mode in the distribution, D 2 50 is the volume median diameter of the second particle mode within the distribution.
[0110] In some embodiments, the electrode is an extruded electrode. In other embodiments, the electrode is a hot rolled electrode. In other embodiments, the electrode is prepared by die extruding the electrode precursor composition according to the first aspect to form a film.
[0111] In some embodiments, the electrode is a cathode.
[0112] All compositional choices and preferences set out above for the electrode precursor composition of the first aspect with respect to the characteristics of the various components of the composition that are not altered during processing of the precursor composition apply equally to the electrode of the second aspect.
[0113] Regarding the amount of components in the electrode of the second aspect, those skilled in the art will appreciate that these amounts may be slightly different from the amounts in the corresponding compositions of the first aspect due to the loss of some volatile components of the precursor composition during the heat treatment of the electrode. In general, it has been observed that about 10-20% by volume of the volatile portion of the precursor composition is lost during the treatment. As a result, the weight or volume fraction of the remaining components accounts for a slightly higher proportion of the entire electrode composition than the precursor composition before the treatment. In general, a given component of the composition after heat treatment can be increased by up to 4% by volume. Therefore, for example, a component that initially constitutes 10% by volume of the precursor composition can constitute greater than 10% by volume of the electrode composition after volatilization loss during the heat treatment, and up to 14% by volume. The technician will be able to easily calculate the expected proportion of each component in the final electrode composition based on the expected or measured volatile component loss.
[0114] In some embodiments, processing comprises heat treatment or extrusion.
[0115] In some embodiments, the thermal treatment comprises passing the electrode precursor composition through a roller assembly at a temperature of at least 50° C., e.g., at least 60° C., at least 70° C., at least 80° C., at least 90° C., or at least 100° C. In some embodiments, the thermal treatment comprises passing the electrode precursor composition through a roller assembly at a temperature of up to 150° C., e.g., up to 140° C., or up to 130° C. In some embodiments, the thermal treatment comprises passing the electrode precursor composition through a roller at a temperature of 50° C. to 150° C., e.g., 60° C. to 150° C., 70° C. to 150° C., 80° C. to 150° C., 80° C. to 140° C., 90° C. to 140° C., 100° C. to 140° C., or 110° C. to 130° C.
[0116] The roller assembly may include two rollers separated by a small distance so that the electrode is pressed into a thin film as it passes over the rollers.
[0117] In some embodiments, the heat treatment comprises extruding the electrode. In some embodiments, the heat treatment comprises extruding the electrode using an extrusion device, the extrusion device comprising one or more screw feed sections and an extrusion die. In some embodiments, the temperature of the die is at least 50°C, for example, at least 60°C, at least 70°C, at least 80°C, at least 90°C or at least 100°C. In some embodiments, the temperature of the die is up to 150°C, for example, up to 140°C or up to 130°C. In some embodiments, the temperature of the die is from 50°C to 150°C, for example, from 60°C to 150°C, from 70°C to 150°C, from 80°C to 150°C, from 80°C to 140°C, from 90°C to 140°C, from 100°C to 140°C or from 110°C to 130°C.
[0118] In some embodiments, the thickness of the electrode is less than 150 μm, such as less than 100 μm, less than 90 μm, less than 80 μm, or less than 70 μm. In some embodiments, the thickness of the electrode is 40 to 150 μm, such as 40 to 100 μm, 40 to 90 μm, 40 to 80 μm, 40 to 70 μm, or 50 to 70 μm.
[0119] In some embodiments, the electrode has a thickness of 40 to 150 μm, e.g., 40 to 100 μm, 40 to 90 μm, 40 to 80 μm, 40 to 70 μm, or 50 to 70 μm, and comprises the electrochemically active material in an amount of 62 to 75 vol %, e.g., 62 to 70 vol %, 62 to 69 vol %, 62 to 68 vol %, or 64 to 69 vol %, of the electrode precursor composition.
[0120] In some embodiments, the electrode has a porosity of less than about 5% by volume. In some cases, the porosity of the electrode is less than 5% by volume, less than 3% by volume, or less than 2% by volume. In other words, the volume density of the electrode can be at least 95% of the density of a completely non-porous electrode, suitably at least about 97% or 98%.
[0121] In some cases, the extruded electrode may form part of an extruded monolith that includes one or more other layers present in an electrochemical cell. For example, the monolith may include a separator layer, and / or may include another electrode (i.e., the extruded monolith may include a cathode and an anode). Different layers may be coextruded and have different compositions from each other.
[0122] A third aspect of the invention provides an electrochemical secondary battery cell comprising an electrode according to the second aspect. The battery cell may be an alkali metal ion secondary battery cell, such as a sodium ion secondary battery cell or a lithium ion secondary battery cell. Preferably, the battery cell is a lithium ion secondary battery cell. In some embodiments, the electrochemical secondary battery cell comprises a first electrode according to the second aspect, wherein the first electrode is a cathode, and a second electrode according to the second aspect, wherein the second electrode is an anode, and an electrolyte between the cathode and the anode. In some embodiments, the electrochemical secondary battery cell comprises an electrode according to the second aspect, which is laminated with a current collector such as a metal foil.
[0123] A fourth aspect of the present invention provides an electrochemical energy storage device comprising an electrochemical secondary battery cell according to the third aspect. In some embodiments, the electrochemical energy storage device is a battery. In some embodiments, the electrochemical energy storage device is a lithium-ion battery.
[0124] A fifth aspect of the present invention provides a method for preparing an electrode for an alkali metal ion secondary battery cell, comprising:
[0125] mixing a polymer, a solvent component and an electrochemically active material to form an electrode precursor composition according to the first aspect; and
[0126] The electrode precursor composition is heat treated to form an electrode film.
[0127] In some embodiments, the electrode film has a thickness of 500 to 700 μm.
[0128] In some embodiments, the method further comprises cutting the electrode film to form electrodes of predetermined dimensions.
[0129] In some embodiments, the method further includes performing a second heat treatment step on the cut film to reduce the thickness of the film to a range of 50 to 70 μm.
[0130] In some embodiments, the temperature during heat treatment is 100 to 140°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0131] Figure 1 Schematic illustration of the possible increase in particle loading by optimizing the particle size distribution as a function of viscosity.
[0132] Figure 2 A rate graph of a battery cell comprising an electrode according to the invention measured at 30° C. is shown.
[0133] Figure 3 An electrode according to the invention is schematically illustrated.
[0134] Figure 4 The particle size distribution of the primary NMC cathode active material used in the Examples is shown.
[0135] Figure 5 The particle size distribution of the secondary NMC cathode active material used in the Examples is shown.
[0136] Figure 6 The particle size distribution of the three-grade NMC cathode active material used in the Examples is shown.
[0137] Figure 7 The particle size distribution of the four-grade NMC cathode active material used in the Examples is shown.
[0138] Figure 8 The particle size distribution of the five-grade NMC cathode active materials used in the Examples is shown. DETAILED DESCRIPTION
[0139] Example
[0140] For all samples tested, the active material, conductive carbon, polymer and electrolyte were first weighed and mixed by hand until the mixture was uniform and free of lumps. The mixture was then fed into a twin screw extruder with three mixing zones at several intervals. The body of the twin screw extruder was maintained at 120 degrees on the mixing zone, tilted 40 degrees from the input port, and dropped to 80 degrees at the outlet. After the material was fed into the twin screw extruder, it was collected as a granular mixture.
[0141] The granular mixture was then rolled into a film. The precursor material was sandwiched between two sheets of polyester film and fed through a nip mill at 120°C, with the nip set to ensure that the material was pressed to a thickness of 600 μm.
[0142] This 600 μm thick precursor film was then cut into 500 mm x 10 mm to evaluate the ability to form thin films. This portion of the film was then fed into the same hot roller assembly with the rollers set at a smaller distance to produce a film of the target thickness, typically 50-70 μm depending on the recipe.
[0143] The formulations that failed to form a film were observed to fail at different steps in the process, but generally they failed at forming a 600 μm thick precursor film. This failure was usually manifested as uneven film formation, often much thicker than expected, often with damage to the carrier film during handling. In some cases, the heated rollers of the assembly were blocked from turning, and film formation was not possible.
[0144] Active Materials
[0145] Five grades of lithium nickel manganese cobalt oxide (NMC) were used in the testing, each with a different particle size distribution.
[0146] "NMC Level #1" is a Figure 4 Bimodal particle size distribution of lithium-nickel-manganese-cobalt-oxide shown. The ratio of the volume fraction of the larger particle mode to the volume fraction of the smaller particle mode is 9.31. Material parameter D 1 50 / D 2 50 It is 3.30.
[0147] "NMC Level #2" is a Figure 5 Monomodal particle size distribution of lithium-nickel-manganese-cobalt-oxide shown. The median particle size is 11.27 µm.
[0148] "NMC Level #3" is a Figure 6 Bimodal particle size distribution of lithium-nickel-manganese-cobalt-oxide shown. The ratio of the volume fraction of the larger particle mode to the volume fraction of the smaller particle mode is 0.74. Material parameter D 150 / D 2 50 It is 2.87.
[0149] "NMC Level #4" is a Figure 7 Bimodal particle size distribution of lithium-nickel-manganese-cobalt-oxide shown. The ratio of the volume fraction of the larger particle mode to the volume fraction of the smaller particle mode is 1.01. Material parameter D 1 50 / D 2 50 It is 2.36.
[0150] "NMC Level #5" is a Figure 8 Monomodal particle size distribution of lithium-nickel-manganese-cobalt-oxide shown. The median particle size is 14.23 µm.
[0151] The particle size distribution of each NMC grade was measured using a Malvern Mastersizer 3000, using the light scattering method set out in ASTM B822-20, applying Mie scattering theory. Individual particle patterns within each grade were then resolved by peak fitting.
[0152] Example 1
[0153] The electrode precursor compositions shown in Table 1 were prepared and tested according to the above method.
[0154] Each composition contained ultra-high molecular weight (>100 kDa) poly(methyl methacrylate) (PMMA) as the polymer.
[0155] The carbon additive is carbon black.
[0156] The electrolyte is a mixture of carbonate solvent, lithium salt and additives as described earlier in the specification.
[0157] Table 1
[0158]
[0159] The results for each composition during the film formation process are listed below in Table 2. "Pass" indicates that the composition was successfully formed into a film by the above-described hot roll method. "Fail" indicates that the tested precursor composition was not likely to form a film.
[0160] Table 2
[0161]
[0162] The results in Table 2 show that compositions containing bimodal electrochemically active materials can be successfully processed into thin films at higher material loadings. A material loading of 64 vol% was achieved with NMC Grade #1 (Compositions 1-3), with failures observed only when the material loading was pushed to 66 vol% or higher (Compositions 4-6). An even higher material loading of 68 vol% was achieved with NMC Grade #3 (Compositions 7-9), with no failures observed for any of the tested compositions containing this material.
[0163] Comparative compositions A and B containing the unimodal electrochemically active material NMC Grade #2 could be processed into thin films at a relatively low material loading of 60 vol%, but failed at a loading of 64 vol%.
[0164] It is clear from these results that the presence of bimodal electrochemically active materials allows for higher loadings of active material without causing failure of the electrode formation process. The composition containing material NMC grade #3 performed particularly well, with loadings of 68 volume % being possible.
[0165] Example 2
[0166] The following composition (Composition 10) was prepared:
[0167]
[0168] The formulation components are mixed together in a single tank before being fed into the extruder.Alternatively, each individual component can be fed into the extruder individually through individually controlled feed systems.
[0169] The powder mixture is then fed into the extruder at a specific controlled rate. In this case, a feed rate of 400-500 g / hour was used.
[0170] The first element of the extruder, the twin-screw compounding section, is used to melt and mix the composition. Its temperature is set to 110°C to fully melt the gel component, and the RPM is set high enough to ensure < 80% torque (in this case set to 100 RPM). The twin-screw design includes three mixing zones, providing the high shear required to fully mix the materials.
[0171] The second element of the extruder, the single screw, is set to provide constant flow / pressure and compression of the material. The speed of the screw is set low enough to minimize pressure variations, and high enough to avoid material buildup in the twin screws. In this case, it is set to 25 RPM. The temperature is set high enough to keep the material in the melt phase, in this case 110°C.
[0172] The third part of the extruder is the film die. The purpose of the film die is to make the material extruded by the single screw into a tube shape and widen and flatten it into a film of the required size. In this case, the final size of the die used is 50mm×0.6mm. The temperature of the die is set to 120℃.
[0173] Example 3
[0174] The following composition (Composition 11) was prepared:
[0175]
[0176] The extrusion method used in Example 3 is the same as that in Example 2.
[0177] By repeating the experiment in Example 2 using 84.4 wt % bimodal cathode material (NMC grade #4), it was observed that while the extrusion was still not completely defect free, the pressure at the die inlet (indicative of viscosity / ease of extrusion) was lower and the film quality was improved.
[0178] Example 4
[0179] The extruded electrodes from Example 3 were characterized by a number of key metrics. Density measurements were performed primarily by manual weight / volume measurements and secondarily by helium pycnometers. These were compared to theoretical density measurements calculated from the recipe.
[0180] Using TGA, it was observed that the solvent (ethylene carbonate) content in the final electrode film was lower than in the initial formulation. This was determined by weighing the mass loss of the sample at 200°C. This indicated that a small portion of the solvent evaporated during the extrusion process, amounting to approximately 1.7% of the total formulation weight, reducing the total solvent content from 9.7% to ~8%. This value was used in the corresponding formulation density calculation.
[0181]
[0182] This density characterization concludes that the material has no (or negligibly small) pores. A formulation density much higher than the measured density would indicate pores. Small amounts of solvent are lost during the manufacturing process, and this loss does not appear to cause pores.
[0183] Example 5
[0184] In this example, the electrode material made in Examples 2-4 above was tested in a battery cell. To test the electrochemical performance of this electrode, the material was laminated onto aluminum foil. To achieve this, the foil was first primed with a 3% primer solution of PVDF5130 in NMP. This was applied by soaking a cotton bud to achieve a very thin layer. When attempting to measure the thickness of this layer, it was undetectable either by micrometer measurement or by weighing a sample of the primed foil. This indicates that the thickness of the layer is submicron.
[0185] The purpose of this primer layer is to achieve adhesion between the electrode and the current collector foil.
[0186] The current collector-electrode laminate is soaked in electrolyte to ensure the presence of the salt within the electrode, however, an alternative approach is to include the salt in the formulation during the extrusion stage.
[0187] The laminate was punched into 12.8 mm discs and assembled into a Swagelok test cell with a glass fiber separator and a lithium metal anode. 100 µL of additional electrolyte was added to allow lithium ions to pass between the anode and cathode.
[0188] Testing of this half-cell made it possible to measure the usable capacity of the cell, which showed values slightly exceeding 170 mAh / g of active material.
[0189] In addition, this half-cell was rate tested at 30°C, showing that >80% of the capacity can be obtained at 1C (see Figure 2 ).
[0190] A schematic diagram of an electrode according to the invention is shown in Figure 3 , where there is a bimodal particle size distribution of electroactive material (1a, 1b) disposed in a conductive polymer gel matrix (2) which also includes a conductive additive (3).
[0191] The electrodes can be extruded onto the current collector (4). Figure 3 Shown in.
Claims
1. An electrode precursor composition for an alkali metal ion secondary battery cell, comprising: polymer-solvent gel matrix phase; and a dispersed phase comprising an electrochemically active material; Among them, the electrochemically active material has D 1 50 / D 2 50 Multimodal particle size distribution ranging from 2 to 15; Among them, D 1 50 is the volume median diameter of the first particle mode in the distribution, D 2 50 is the volume median diameter of the second particle mode in the distribution.
2. The electrode precursor composition according to claim 1, wherein The ratio of the volume fraction of the first particle mode to the volume fraction of the second particle mode is 0.6 to 15.
3. The electrode precursor composition according to claim 2, wherein The ratio of the volume fraction of the first particle mode to the volume fraction of the second particle mode is 2 to 4.
4. An electrode precursor composition according to any one of the preceding claims, wherein The electrochemically active material has D 1 50 / D 2 50 Multimodal particle size distribution in the range of 6 to 8.
5. An electrode precursor composition according to any one of the preceding claims, wherein The electrochemically active material constitutes at least 60 volume % of the electrode precursor composition.
6. An electrode precursor composition according to any one of the preceding claims, wherein The dispersed phase also includes a conductive additive.
7. The electrode precursor composition according to claim 6, wherein The conductive additive includes one or more of carbon black and graphite.
8. The electrode precursor composition according to claim 6 or 7, wherein The conductive additive is present in an amount of about 1.5 wt % to about 2.5 wt % based on the total weight of the electrode precursor composition.
9. An electrode precursor composition according to any one of the preceding claims, wherein The polymer-solvent gel matrix phase comprises a mixture of a gelling polymer and a liquid electrolyte, wherein the weight ratio of electrolyte:polymer is 2 to 6.
10. The electrode precursor composition according to claim 9, wherein The polymer sol gel matrix phase comprises 15 to 25 volume percent of the gelling polymer, based on the total volume of the polymer-solvent gel matrix phase.
11. The electrode precursor composition according to claim 9 or 10, wherein The liquid electrolyte includes a solvent including one or more cyclic or linear carbonate compounds.
12. An electrode precursor composition according to any one of the preceding claims, wherein The polymer-solvent gel matrix phase constitutes 20% to 50% by volume of the electrode precursor composition.
13. An electrode precursor composition according to any one of the preceding claims, wherein The electrochemically active material is a positive electrode active material.
14. An electrode precursor composition according to any one of the preceding claims, wherein The electrochemically active material is a lithium transition metal oxide material.
15. An electrode precursor composition according to any one of the preceding claims, wherein The electrochemically active material has a bimodal particle size distribution.
16. An electrode precursor composition according to any one of the preceding claims, wherein The polymer-solv gel matrix phase comprises one or more gelling polymers selected from the group consisting of poly(ethylene glycol dimethacrylate), poly(ethylene glycol diacrylate), poly(propylene glycol dimethacrylate), poly(propylene glycol diacrylate), poly(methyl methacrylate) (PMMA), poly(acrylonitrile) (PAN), polyurethane (PU), poly(vinylidene fluoride) (PVdF), poly(vinylidene fluoride-hexafluoropropylene) (PvDF-HFP), poly(ethylene oxide) (PEO), poly(ethylene glycol dimethyl ether), poly(ethylene glycol diethyl ether), poly[bis(methoxyethoxyethoxy)-phosphazene], poly(dimethyl poly(4-phenylenesulfonyl)(trifluoromethanesulfonyl)imide-co-methoxy-polyethylene glycol acrylate] (Li[PSTFSI-co-MPEGA]), sulfonated polyphenylene oxide (PPO), N,N-dimethylacrylamide (DMAAm), lithium 2-acrylamido-2-methyl-1-propane sulfonate (LiAMPS), poly(2-acrylamido-2-methylpropane sulfonate-co-vinyltriethoxysilane), polyethylene oxide (PEO) / poly(lithium sorbate), PEO / poly(lithium mucate), PEO / [polysorbate)+BF3), PEO copolymers, PEO terpolymers, and NIPPON SHOKUBAI® polymers.
17. An electrode precursor composition according to any one of the preceding claims for use in a lithium ion secondary electrochemical cell.
18. An electrode for an alkali metal ion secondary battery cell, comprising: polymer-solvent gel matrix phase; and a dispersed phase comprising an electrochemically active material; Among them, the electrochemically active material has D 1 50 / D 2 50 Multimodal particle size distribution ranging from 2 to 15; Among them, D 1 50 is the volume median diameter of the first particle mode in the distribution, D 2 50 is the volume median diameter of the second particle mode in the distribution.
19. The electrode according to claim 18, produced by processing the electrode precursor composition according to any one of claims 1 to 16 to form a film.
20. The electrode according to claim 19, wherein The treatment includes heat treatment or extrusion.
21. An electrochemical secondary battery cell comprising an electrode according to any one of claims 18-20.
22. An electrochemical energy storage device comprising the electrochemical secondary battery cell according to claim 21.
23. A method for preparing an electrode for an alkali metal ion secondary battery cell, comprising: mixing a polymer, an electrolyte and an electrochemically active material to form an electrode precursor composition according to any one of claims 1 to 16; and The electrode precursor composition is heat treated to form an electrode film.
24. The method according to claim 23, wherein: The electrode film has a thickness of 500 to 700 μm.
25. The method according to claim 23 or 24, further comprising cutting the electrode film to form electrodes of predetermined size.
26. The method according to any one of claims 23 to 25, further comprising performing a second heat treatment step on the cut film to reduce the film thickness to within the range of 50 to 70 μm.
27. The method according to any one of claims 23 to 26, wherein: The temperature during the heat treatment is 100 to 140°C.